Pengaruh Motivasi Kerja, Kepuasan Kerja, Lingkungan Kerja, Hubungan Kerja, dan Tingkat Pendidikan Terhadap Kinerja Karyawan Dengan Gaya Kepemimpinan Sebagai Variabel Mediasi di Perusahaan Manufaktur di Kota Batam - Yuswardi, Yuswardi; Farid, Ridhayati; Astuty, Dessy (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
A major manufacturing opportunity in Indonesia lies in Batam City, with 70% of electronics production. Six major companies, such as PT Epson Batam and PT Schneider Electric, play a key role. Human resource management (HRM) is a crucial factor in the company's success. Employees who are motivated, satisfied, work in a conducive environment, have good working relationships, and a good level of education can improve company performance. Work motivation, job satisfaction, work environment, work relationships, and employee education level affect performance, with leadership style as a mediator. SEM-PLS analysis shows that these variables have a significant influence. Leadership style acts as a strong mediator, linking motivation, satisfaction, environment, relationships, and education with employee performance. The findings provide important insights for companies in developing HR management strategies to improve performance and competitiveness in the manufacturing industry. A large manufacturing industry opportunity in Indonesia is located in Batam City, with 70% of electronics production. Six major companies, such as PT Epson Batam and PT Schneider Electric, play a key role. Human resource (HR) management is a crucial factor in the company's success. Employees who are motivated, satisfied, work in a conducive environment, have good working relationships, and a good level of education can improve company performance. Work motivation, job satisfaction, work environment, work relationships, and employee education level affect performance, with leadership style as a mediator. SEM-PLS analysis shows that these variables have a significant influence. Leadership style acts as a strong mediator, linking motivation, satisfaction, environment, relationships, and education with employee performance. The findings provide important insights for companies in developing HR management strategies to improve performance and competitiveness in the manufacturing industry.